FACTORS AFFECTING SURVIVAL IN PATIENTS WITH OESOPHAGEAL ATRESIA AND TRACHEO-OESOPHAGEAL FISTULA - Haq, Anwar -ul-; ullah, Ubaid; Akhter, Nadeem; ullah, Sami; Javeria, Javeria; Jan, Iftikhar A.; Abbasi, Zaheer (Journal of Ayub Medical College Abbottabad, 2009)
Objective: To evaluate the various factors affecting survival in babies with oesophageal atresia and tracheo-oesophageal fistula. Design: Descriptive study. Setting: The study was carried out at the Department of Paediatric Surgery, The Children's Hospital, Pakistan Institute of Medical Sciences (PIMS), Islamabad from March 2004 to March 2005. Patients and Methods: All neonates with oesophageal atresia (EA) and tracheo-oesophageal fistula (TEF) during the study period were included in the study. Patients having isolated EA were excluded. A total of 80 patients were included in the study. Patients were received from the emergency department, OPD and Neonatal ICU. Diagnosis was confirmed by passing a radio opaque orogastric tube. Investigations were done to look for other associations. After stabilisation, right thoracotomy was performed, fistula was ligated and divided. An attempt was made to do a primary oesophago-oesopahgostomy. Nasogastric feeding was started on 2nd post-operative day. A contrast oesophagogram was performed on the 7th postoperative day and having ruled out leak, oral feeding was started. Results: Out of the total, 33 (41%) survived and 47 (58%) patients died. Out of 47 deaths 20 (25%) died before surgery and 27 (34%) died after surgery. Mean follow up period was 6 months. Sixteen (20%) patients had anastomotic leak, 24 (30%) had anastomotic stricture, and 64 (80%) patients had postoperative pneumonia. Conclusion: We conclude that proper antenatal check ups will detect the problem early, avoid home deliveries and hence improve survival. Pneumonitis and septicaemia significantly affect survival. Availability of ICU is one of the main determinants of survival. The likely cause of high mortality rate in pre-operative patients in our series is non-availability of NICU due to limited space in our setup. Keywords: Oesophageal atresia, tracheo-oesophageal fistula, survival, neonates